PERANCANGAN STRUKTUR ATAS JEMBATAN KOMPOSIT BOX GIRDER BAJA BERDASARKAN PEMBEBANAN MENURUT AASHTO 2010 DAN RSNI T-02-2005 - , JEFFRY DAUD BARRUNG ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Composite steel box girder bridge is a bridge with a girder which is connected to the floor slab using shear connector where the girder on the bridge is a steel box girder. In this study used AASHTO 5th Edition 2010 regulations in bridge design. For loading bridge used RSNI T-02-2005 and AASHTO 2010. This study aims to compare the two rules used in loading in the design of composite box girder steel bridge. This study performed by means of library studies to rule RSNI T-02-2005, AASHTO 2010, and other regulations related to planning as the vehicle floor plate bridge, elastomer placement planning, and others. This review process is divided into several stages. First, determining bridgeâs technical data and structural modeling. In the next sequence, design based on AASHTO 2010 to determine the capacity of bridge strength. Loads are applied on the bridge based on RSNI T-02-2005 and AASHTO 2010. The final stage of this study compare the loads value based on RSNI and AASHTO. The results of this study is design of composite box girder steel bridge meets the requirements of the load according to RSNI and AASHTO . From the comparison of loading according to the rule found that the ratio of moments and shear forces of AASHTO 2010 to RSNI T - 02-2005 are 102.45 % and 125.89 % . Imposition according to AASHTO greater than RSNI because the forces resulting from the imposition of rules using AASHTO 2010 is greater than using RSNI 2005 . It is aimed at the design of the bridge to increase the strength of the bridge with the imposition of greater value .